FABRICATION AND IN VITRO EVALUATION OF METFORMIN ENTRAPPED SUSTAINED RELEASE AMMONIO METHACRYLATE COPOLYMER MICROPARTICLES PREPARED BY NON-AQUEOUS EMULSIONSOLVENT EVAPORATION TECHNIQUE - A.B. LOKHANDE; T.A. DESHMUKH; V.R. PATIL (International Journal of Pharma and Bio Sciences, 2013)
Metformin hydrochloride is an orally administered first line drug which commonly used in the management of type-2 diabetes. To overcome the side effects of it due to high/repeated dose and patient inconvenience, the sustained release microparticles of metformin loaded RS100 were developed. The method used to prepared microparticles was novel oil in oil technique. Obtained microparticles were characterized by the different tests like Size, Encapsulation efficiency, Drug content, Percent yield determination, FE-SEM, FTIR, XRD, Dissolution study and Drug release kinetics. The obtained particles were from 236 to 313 µm in size, above 90% encapsulation efficiency and percentage yield was observed, drug and polymer not interacted, microparticles were in amorphous nature and drug-polymer influenced on dissolution profile. The more sustained batch followed Higuchi model. The statistical significance of the difference were tested by one-way ANOVA where p≤ 0.05.